International marketing - Cateora, Philip R.; Graham, John L. (Boston McGraw-Hill/Irwin, 2005)
Contents: an overview; the cultural environment of global markets; assessing global market opportunities; developing global marketing strategies; implementing global marketing strategies; supplementary material.
Includes bibliographical references and indexes
Keywords: Quản trị kinh doanh